Quantum Dots in Ophthalmology: A Literature Review. (3rd October 2019) - Sarwat, Sidra; Stapleton, Fiona; Willcox, Mark; Roy, Maitreyee
ABSTRACT: Purpose : The aim of the current review was to summarize the current applications, the latest advances and importantly, highlight research gaps in the use of quantum dots in the eye. Quantum dots are nanoscale semiconductor crystals with characteristic size and tunable optical properties, which deliver bright and stable fluorescence suitable for bioimaging and labelling. Methods : A systematic search was conducted following the PRISMA guidelines. This review systematically searched published data to summarize the characteristics and applications of quantum dots in ophthalmology. Two hundred and eighty published articles were initially selected for this review following searches using the criteria quantum dots AND nanoparticles AND ophthalmology in the databases PubMed, MEDLINE, Scopus, Embase and Web of Science. Results : After duplicates were removed, a total of 22 eligible articles were included for the review. Quantum dots potentially provide a range of diagnostic and therapeutic applications in ophthalmology. Quantum dots offer visible and near-infrared emission, which is highly desirable for bioimaging, due to reduced light scattering and low tissue absorption. Their applications include in vivo bioimaging, labelling of cells and tissues, delivery of genes or drugs and as antimicrobial composites. Conclusion : Quantum dots have been used in ophthalmology for bioimaging, electrical stimulation and tracking of gene/stems cells, and ocular lymphatics. However, there is no detailed description of their desirable characteristics for use in ophthalmology, and there is limited information about their cytotoxicity to ocular cells and tissues.